EFFORTS TO MAINTAIN QUALITY AND EXTEND THE SHELF LIFE OF TANGERINE CITRUS FRUITS WITH PACKAGING AND STORAGE TEMPERATURE - Sundari, Retno; Sumiasih, Inanpi Hidayati (Universitas Trilogi, 2023)
Citrus fruit is a non-climacteric fruit, this fruit must be picked when it is ripe optimally. Post-harvest methods include harvest collection, washing and cleaning, quality classification, packaging and storage. Apart from being expected to have a good shelf life, citrus fruit must also have hight quality and be able to maintain its nutritional content for consumers' needs. The aim of this research was to determine the effect of storage and packaging temperatures on changes in the quality and shelf life of Tangerine Citrus. The research was conducted in October to November 2021 at the Laboratory of Agrotechnology, Trilogi University. This research method uses a randomized block design consisting of two factors and three replications. The first factor is that packaging consists of two levels, namely packaging using wrapping and non-wrapping. The second factor is temperature which consists of two levels: 15°C and 25°C. The result of this study is that citrus with a non-wrapping treatment with a storage temperature of 15 oC is the best treatment and can be consumed up to 8 days after treatment, this can be seen from some of the lowest weight shrinkage percentage, scoring appearance, color, and taste that is still acceptable to consumers compared to other treatments.